Assessment of Heavy Metal Concentrations in Roadside Soils from Mafraq, Jordan - Al-Sarhan, Ahmed; Al-Massaedh, "Ayat Allah"; Al-Momani, Idrees Faleh (Indonesian Journal of Chemistry, 2024)
In the present study, the concentrations of nine heavy metals (Cr, Cd, Cu, Mn, Pb, Co, Fe, Ni, and Zn) in roadside soils were measured by flame atomic absorption spectroscopy (FAAS). Roadside soils were collected during the summer semester from Mafraq, Jordan (N = 97). Four sampling sites were selected for this study, including commercial area, industrial area, residential area, and Irbid-Mafraq highway. The average metal concentrations (±SD) in the collected soils were 16840 (± 9479), 40 (± 40), 99 (± 44), 478 (± 155), 60 (± 62), 2 (± 1), 73 (± 23), 14 (± 5), and 45 (± 13) mg/kg for Fe, Cu, Zn, Mn, Pb, Cd, Cr, Co, and Ni, respectively. The results of this study revealed that the highest Mn, Cu, Co, Ni, Zn, Fe, and Pb concentrations were found in the industrial area, and the highest Cd concentration was found at the Irbid-Mafraq highway. The values of the enrichment factors for Zn, Cr, Cd, and Ni in the collected roadside soils were found to be higher than 10, confirming the presence of anthropogenic pollution in the studied areas. The results of this study were also compared with other studies performed in different countries in the world.